Geneza opere Gorenjski slavček - Pompe, Gregor (Muzikološki zbornik, 2015)
Among Slovenian operas of the 19th century Anton Foerster's Gorenjski slavček seems to be closest to the popular genre of national opera. The article takes as its starting point the questions of work genesis, which went through different phases: from the early operetta variant to the final through-composed opera. In this light, the fragmentary score, kept in the music department of Slovenian National Library is interpreted as an important step; Foerster had clearly been contemplating the opera form of his operetta for almost two decades before completing the final score.
Keywords: 19.st.; Foerster, Anton; nacionalna opera; slovenska opera